化简求值:3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,其中a=-2 ,十分钟内回答加悬赏!快

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/03 05:45:10
化简求值:3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,其中a=-2 ,十分钟内回答加悬赏!快
x){3g62H6Ԍ3534uA{˳Ow,{ںir[]C6XCj.QP%ڦ$Z(|KF 1@6`6~{gT~O.D^0X.LbqQ8 P)k ; v

化简求值:3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,其中a=-2 ,十分钟内回答加悬赏!快
化简求值:3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,其中a=-2 ,十分钟内回答加悬赏!快

化简求值:3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,其中a=-2 ,十分钟内回答加悬赏!快
3(a+1)^2-5(a+1)(a-1)^2+2(a-1)^2,因为a=-2,直接带入到a+1=-1,可得
=3(-1)^2-5(-1)(a-1)^2+2(a-1)^2
=3+5(a-1)^2+2(a-1)^2
=3+7(a-1)^2
=3+7*(-3)^2
=3+7*9
=66

3(a+1)^2-5(a+1)(a-1)+2(a-1)^2
={3(a+1)-2(a-1)}{(a+1)-(a-1)}
=(3a+3-2a+2)(a-a+1+1)
=2(a+5)
=2(-2+5)
=6